Comparative Analysis of Housing Production Processes in the Context of Actor-Network Theory (ANT) in Urban Renewal Areas - Ayşegül Baghal; Candan Çınar Çıtak (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2022)
Policies and strategies devoid of participatory planning principles applied in the urban transformation process; accelerated the formation of unplanned, unhealthy, and identity-less urban environments; It has caused the physical, socio-cultural, and psychological needs of people not to be adequately met. The main purpose of the study is to create a strategic framework by taking the housing production systems developed on a local and global scale, including all the actors that should be in the urban transformation areas, with the perspective of the Actor-Network Theory, by making comparative analyzes of the case studies in which the causal relationships are analyzed. ANT, which is one of the approaches to solving the social relations system, has been evaluated as a research methodology that can reveal the whole network of relations between the actors, objects, and things involved in the housing production process, and the examination of ANT-based housing production models is planned within the scope of the study. It is aimed to question the applicability in our country by researching housing production models in urban transformation areas and raising them to the global level based on the theoretical framework.